TOWARD AN INCLUSIVE INDONESIA: SOLUTIONS FOR IMPLEMENTING MULTICULTURAL EDUCATION - Khairunnisa Nissa; Maira Amelia Maira; Marsya Yarasyimah Marsya; Syifa Nabila Syifa (Journal of Pedagogical Content Knowledge, 2026)
Indonesia, a country with rich cultural diversity, has great potential to serve as a model for the implementation of multicultural education. The diversity of ethnicity, religion, race, and intergroup relations (SARA) is a national treasure, but it also poses a potential for conflict if not managed properly. Multicultural education offers a solution to address this potential conflict and build a more harmonious and inclusive Indonesian society. The research method used in this study to identify solutions for implementing multicultural education is descriptive qualitative research, specifically in the context of a literature review. A literature review is the initial stage of research that involves investigating and evaluating previous studies relevant to the current research topic. Its primary objectives are to provide a theoretical framework, define the scope of the research, and identify research gaps that need to be addressed. Solutions for enhancing multicultural education include integrating multicultural educational content into all subjects, providing training for educators, fostering a multicultural culture within schools, encouraging community participation, and utilizing interactive teaching methods. Indonesia, as a country with rich cultural diversity, has great potential to serve as a model for the implementation of multicultural education. The implementation of multicultural education in Indonesian schools faces a number of fairly complex challenges. Promoting Intercultural Dialogue: Teachers can create a classroom environment that promotes dialogue and intercultural exchange.